Phonon anomalies in optical spectra of LiNbO3 single crystals - ANDREJA VALCIC; IVANA HINIC; RADOS GAJIC; ALEKSANDAR GOLUBOVIC (Journal of the Serbian Chemical Society, 2004)
LiNbO3 single crystals were grown by the Czochralski technique in an air atmosphere. The critical crystal diameter Dc = 1.5 cm and the critical rate of rotation wc = 35 rpm were calculated by equations from the hydrodynamics of the melt. The domain inversion was carried out at 1430 K using a 3.75 V/cm electric field for 10 min. The obtained crystals were cut, polished and etched to determine the presence of dislocations and single domain structures. The optical properties were studied by infrared and Raman spectroscopy as a function of temperature. With decreasing temperature, an atypical behaviour of the phonon modes could be seen in the ferroelectrics LiNbO3. The obtained results are discussed and compared with published data.